2019
DOI: 10.1111/jpn.13081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guanidinoacetic acid on growth performance, creatine metabolism and plasma amino acid profile in broilers

Abstract: The objective of this study was to assess the effects of guanidinoacetic acid (GAA) on growth performance, creatine deposition and blood amino acid (AA) profile on broiler chickens. In Exp. 1, a total of 540 one‐day‐old Arbor Acres male broilers (average initial body weight, 45.23 ± 0.35 g) were divided randomly into five treatments with six replicates of 18 chicks each. Broilers were fed corn–soybean meal‐basal diets supplemented with 0, 600, 800, 1,000 or 1,200 mg/kg GAA for 42 days respectively. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The contents of plasma isoleucine, leucine, lysine, phenylalanine, valine, and threonine decreased with the increase in the dietary GAA concentration, which was consistent with the results of He et al [ 38 ]. No significant difference was found in the plasma leucine content between GAA treatments in broilers [ 38 ]. Compared with GAA500, GAA1500 significantly reduced the plasma leucine content in this experiment.…”
Section: Discussionsupporting
confidence: 91%
“…The contents of plasma isoleucine, leucine, lysine, phenylalanine, valine, and threonine decreased with the increase in the dietary GAA concentration, which was consistent with the results of He et al [ 38 ]. No significant difference was found in the plasma leucine content between GAA treatments in broilers [ 38 ]. Compared with GAA500, GAA1500 significantly reduced the plasma leucine content in this experiment.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, GAA addition could be particularly useful in diets for fast-growing broiler strains because of their high energy and nutrient demands for the supply of muscle creatine ( Michiels et al., 2012 ). In other research, the positive effects of dietary GAA on the growth performance of broiler chickens were found, and the conversion of GAA into creatine was identified by higher blood and muscle creatine concentrations ( He et al., 2019 ; Zhang et al., 2019 ). On the other hand, the Arg-sparing properties of GAA are becoming increasingly important in a variety of situations, including high altitude and temperature stress, which both raise Arg requirements ( Khajali et al., 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…It has been suggested that GAA is a more appropriate feed additive when compared to creatine and Arg since it is less costly than either of these compounds and is more chemically stable than creatine ( Baker, 2009 ). Previous experiments showed that adding 0.6 g/kg of GAA to the diet of broilers reared under normal temperature conditions ( Michiels et al., 2012 ; He et al., 2019 ) or under heat stress ( Amiri et al., 2019 ) led to better weight gain and feed conversion ratio. Accordingly, the inclusion of GAA in the feed, as an Arg-sparing substance, was hypothesized to enhance performance and decrease ascites mortality in broiler chickens raised under cold stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies showed that dietary long-term (>35 d) supplementation with GAA at dose rate of 600 to 1,200 mg/kg can improve the feed conversion efficiency and increase body weight gain of broilers ( Michiels et al, 2012 ; Córdova-Noboa et al, 2018 ; He et al, 2019 ), and even under stress condition ( Majdeddin et al, 2020 ). Faraj et al (2014) reported that dietary addition of 4 to 12 g/kg CMH for a trial period of 42 d can improve birds’ growth performance.…”
Section: Discussionmentioning
confidence: 99%